Ersehnte Einheit, unheilbare Spaltung: Geschlechterordnung und Republik bei Rousseau - Scherl, Magdalena (transcript, 2016)
The political thought of Rousseau – ambiguities and abysses of his republic from the perspectives of gender and desire theory.